Kaempferol-induces vasorelaxation via endothelium-independent pathways in rat isolated pulmonary artery - Mahobiya, Archana; Singh, Thakur Uttam; Rungsung, Soya; Kumar, Tarun; Chandrasekaran, Gokul; Parida, Subhashree; Kumar, Dinesh (Pharmacological reports, 2018)
Kaempferol, a flavonoid, is the essential part of human diet. Flavonoids have different pharmacological activities like cardioprotective, anti-inflammatory and anti-oxidant. The aim of current study was to investigate vasorelaxant potential of kaempferol on rat isolated pulmonary artery and to assess the underling mechanisms. Tension experiments were conducted on both the branches of main pulmonary artery of rats. Experiments were done using isolated organ bath system by recording tension with the help of data acquisition system, Power Lab. Kaempferol (10−8–10−4.5M) caused concentration-dependent relaxation (Emax 124.33±4.37%; pD2 5.03±0.084) of endothelium-intact pulmonary artery. In endothelium-denuded arterial rings, relaxation produced by kaempferol was not different from intact artery. L-NAME, indomethacin, combination of L-NAME and indomethacin did not show any effect on kaempferol-induced relaxation. Kaempferol-induced relaxation was reduced (Emax 55.53±7.72%) in 60mMK+ pre-contracted pulmonary arterial rings. Iberiotoxin significantly decreased (Emax 71.68±11.84%) the relaxation response. However, glibenclamide, BaCl2, 4-AP (1mM) and ICI182780 did not reduce the kaempferol-induced relaxation. TEA (10mM) and 4-AP (5mM) significantly reduced relaxation. Kaempferol-induced relaxation was significantly attenuated (Emax 94.92±19.60%) in presence of ODQ. H89 significantly decreased (Emax, 98.38±8.55%) the kaempferol-induced relaxation in rat pulmonary arterial rings. HC067047 and apamin did not show any effect on kaempferol-induced relaxation. In endothelium-denuded K+ (80mM)-depolarized arterial rings, kaempferol (10μM) markedly reduced CaCl2-induced contractions (Emax 35.14±6.53% vs. control 69.04±15.19%). Kaempferol relaxes rat pulmonary artery in endothelium-independent manner through involvement of BKCa channel, sGC, PKA pathways and inhibition of Ca2+-influx through L-type calcium channels.